Adjustments of muscle capillarity but not mitochondrial protein with skiing in the elderly. Issue 4 (28th September 2014) - van Ginkel, S.; Amami, M.; Dela, F.; Niederseer, D.; Narici, M. V.; Niebauer, J.; Scheiber, P.; Müller, E.; Flück, M.
<x xml:space="preserve">Abstract</x> Downhill skiing in the elderly increases maximal oxygen uptake (VO2max) and carbohydrate handling, and produces muscle hypertrophy. We hypothesized that adjustments of the cellular components of aerobic glucose combustion in knee extensor muscle, and cardiovascular adjustments, would increase in proportion to VO2max. Nineteen healthy elderly subjects (age 67.5 ± 2.9 years) who completed 28.5 days of guided downhill skiing over 3 months were assessed for anthropometric variables, cardiovascular parameters (heart rate, hematocrit), VO2max, and compared with controls (n = 20). Biopsies of vastus lateralis muscle were analyzed for capillary density and expression of respiratory chain markers (NDUFA9, SDHA, UQCRC1, ATP5A1) and the glucose transporter GLUT4. Statistical significance was assessed with a repeated analysis of variance and Fisher's post‐hoc test at a P value of 5%. VO2max increased selectively with ski training (+7 ± 2%). Capillary density (+11 ± 5%) and capillary‐to‐fiber ratio (12 ± 5%), but not the concentration of metabolic proteins, in vastus lateralis were increased after skiing. Cardiovascular parameters did not change. Fold changes in VO2max and capillary‐to‐fiber ratio were correlated and were under genetic control by polymorphisms of the regulator of vascular tone, angiotensin converting enzyme. The observations indicate that increased VO2max after recreational downhill ski training is associated with improved capillarity in a mainly recruited muscle group.